Effects of intra-hippocampal injection of interleukin-2 on pain threshold and formaldehyde-induced substance P-like immunoreactivity in periaqueductal gray and spinal cord. - Wu Xuan; Li Hai-di; Li Xi-cheng; Ruan Huai-zhen; Wang Jian (Acta Pharmacologica Sinica, 2016)
AIM: To study the effects of intra-hippocampal injection of interleukin-2 (IL-2) on the substance P-like immunoreactivity (SP-LI) in both periaqueductal gray (PAG) and spinal cord, and on pain threshold in rats. METHODS: Immunohistochemistry technique was used and the paw withdrawal threshold to radiant heat was measured. RESULTS: Microinjection of hIL-2 480 U in hippocampus (Hip) increased the pain threshold (93% +/- 57%, P < 0.01). Injection of formaldehyde (For) in one hindpaw decreased SP-LI neuron number on both sides of PAG (2.9 +/- 2.8 vs 22.1 +/- 0.7, 12.3 +/- 2.0 vs 22.4 +/- 1.0, P < 0.01) and increased SP-LI in ipsilateral spinal cord (0.836 +/- 0.015 vs 0.59 +/- 0.09, P < 0.01). Microinjection of hIL-2 480 U in Hip inhibited the effects of For on the SP-LI on both sides of the PAG (11.3 +/- 2.3 vs 2.9 +/- 2.8, 16.9 +/- 3.4 vs 12.3 +/- 2.0, P < 0.05) and spinal cord (0.71 +/- 0.03 vs 0.836 +/- 0.015, P < 0.01). The combination of intraperitoneal injection of corticotropin and intra-hippocampal injection of IL-2 increased the number of SP-LI neurons in PAG furtherly as compared with IL-2 240 U alone (13.6 +/- 3.6 vs 7.6 +/- 4.3, P < 0.05). CONCLUSION: The analgesic effects of intra-hippocampal injection of IL-2 are mediated, possibly, via the increased of SP in PAG and the decrease of SP in the spinal cord. There is a synergetic relation between IL-2 and corticotropin.